(4-Nitrophenyl)methyl 2,3-dihydro-1H-pyrrole-1-carboxylate: crystal structure and Hirshfeld analysis - Zukerman-Schpector, Julio; Soto-Monsalve, Monica; De Almeida Santos, Regina H.; Garcia, Ariel L. L.; Correia, Carlos Roque D.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
In the title compound, C12H12N2O4, the dihydropyrrole ring is almost planar (r.m.s. deviation = 0.0049 A ˚ ) and is nearly coplanar with the adjacent C2O2 residue [dihedral angle = 4.56 (9˚)], which links to the 4-nitrobenzene substituent [dihedral angle = 4.58 (8˚)]. The molecule is concave, with the outer rings lying to the same side of the central C2O2 residue and being inclined to each other [dihedral angle = 8.30 (7˚)]. In the crystal, supramolecular layers parallel to (105) are sustained by nitrobenzene-C—H...O(carbonyl) and pyrrole-C—H...O(nitro) interactions. The layers are connected into a three- dimensional architecture by π(pyrrole)–π(nitrobenzene) stacking [inter-centroid separation = 3.7414 (10) A ˚ ] and nitro-O...π(pyrrole) interactions.